Perfect ambition, Thomas Bodkin : a life, with particular reference to his influence on the early development of Irish cultural policy - Kelly, Anne (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2002)
This research is an analysis of the development of cultural policy in the context of the Irish life and times of Thomas Bodkin. The research methodology involved the use of primary manuscript material relating to personal, institutional and State papers in archives in Ireland and Britain. Interviews were conducted with relevant individuals, both family members and a number of Bodkin’s former colleagues, friends and acquaintances. This was supported by a literature review of secondary material, including books, journals, periodicals and newspaper files. Bodkin’s bibliography by Alan Denson was an important source and family papers at the National Archives, as well as Bodkin’s own extensive papers at TCD, were central to the research. The research is presented through a combination of a chronological narrative with a thematic approach in which policy interventions are included at relevant points in the text. Bodkin’s life, his family history, his friendships and animosities and his career ambitions, his successes and failures are presented chronologically. This provides a picture of life in the Dublin intellectual world inhabited by Bodkin in the early years of the 20th century. His theories of art, indicated in his prolific writings and lecturing on art are also discussed and placed in context. The themes presented and analysed involve four main areas. Bodkin’s role as a Trustee of the National Gallery and ultimately its Director is analysed and this provides an insight into the management of a key cultural institution at an important stage of its development. Bodkin’s association with Hugh Lane was a most significant one and he was a major figure in the fight to return the Lane pictures to Ireland. Research at the National Gallery in London and at the Public Record Office builds on Bodkin’s book on Lane and subsequent work. The issue has never before been considered from the British perspective and this study draws extensively on the records of the National Gallery in London as well on British Government papers relating to the codicil to Lane’s Will. The benefits of developing art education were frequently outlined by Bodkin and he had a strong interest in design issues. The research examines his role in the design of the new Irish currency in 1927. On the coinage design he worked on a Committee chaired by W.B.Yeats, and Percy Metcalf was selected as the artist who produced the designs for what is now recognised as a successful and aesthetically significant set of coins for the new Irish State. On the note design, Bodkin was active in the selection of John Lavery as the artist and his wife Hazel as the model for the notes. His close friendship with her was a symbiotic one and she worked unsuccessfully to have him appointed as High Commissioner in London shortly after his appointment as Director of the National Gallery. The public response to the two design outcomes was different and this is also a subject of analysis in the research. Bodkin’s time at the National Gallery came to an end in 1935 following a period in which all efforts by him to improve conditions at the Gallery failed. He established the Barber Institute of Fine Arts at the University of Birmingham but continued to influence cultural policy in Ireland. One of his most important policy initiatives involved his report on the arts in Ireland, commissioned by the Government in 1949. This allowed him to draw together the policy proposals he had been articulating for many years but the response of the Government was a limited one. The Arts Council was established and Bodkin’s role in this is analysed and its outcomes discussed. His hopes to return to direct the Council were dashed following a change of Government but his friendship with John A. Costello brought him back in a consultancy capacity to advise on the development of the Council. This was by no means a successful outcome and it undermined the arms-length principle which he and Costello had envisaged for the Council. He was never to return to work in Ireland and died in Birmingham in 1961.
Access restricted on volume 2 due to image copyright concerns. Please consult print copy in the Library.
Keywords: History of Art and Architecture, Ph.D.; Ph.D. Trinity College Dublin